EULAR Sjögren's syndrome disease activity index (ESSDAI): a user guide. Issue 1 (20th February 2015) - Seror, Raphaèle; Bowman, Simon J; Brito-Zeron, Pilar; Theander, Elke; Bootsma, Hendrika; Tzioufas, Athanasios; Gottenberg, Jacques-Eric; Ramos-Casals, Manel; Dörner, Thomas; Ravaud, Philippe; Vitali, Claudio; Mariette, Xavier; et al.
Abstract : The EULAR Sjögren's syndrome (SS) disease activity index (ESSDAI) is a systemic disease activity index that was designed to measure disease activity in patients with primary SS. With the growing use of the ESSDAI, some domains appear to be more challenging to rate than others. The ESSDAI is now in use as a gold standard to measure disease activity in clinical studies, and as an outcome measure, even a primary outcome measure, in current randomised clinical trials. Therefore, ensuring an accurate and reproducible rating of each domain, by providing a more detailed definition of each domain, has emerged as an urgent need. The purpose of the present article is to provide a user guide for the ESSDAI. This guide provides definitions and precisions on the rating of each domain. It also includes some minor improvement of the score to integrate advance in knowledge of disease manifestations. This user guide may help clinicians to use the ESSDAI, and increase the reliability of rating and consequently of the ability to detect true changes over time. This better appraisal of ESSDAI items, along with the recent definition of disease activity levels and minimal clinically important change, will improve the assessment of patients with primary SS and facilitate the demonstration of effectiveness of treatment for patients with primary SS.